Substrate stiffness and particle properties influence cellular uptake of nanoparticles and viruses from the ventral side - Voigt, Jonah L.; Timmer, Jens; Pennarola, Federica; Christian, Joel; Meng, Ning; Blumberg, Johannes; Schwarz, Ulrich S.; Grimm, Dirk; Cavalcanti-Adam, Elisabetta A. (Advanced functional materials, 2024)
It is a long-standing challenge to exploit cellular uptake mechanisms to deliver desired cargo into cells, for example, specific drugs or gene editing techniques. This study introduces a bioinspired material approach where nanoparticles are presented at the ventral side of cells adhering to engineered extracellular matrices. The effect of matrix stiffness on cell adhesion and mechanics, as well as on particle internalization by clathrin-mediated endocytosis (CME), is investigated for varying particle size and surface functionalization. The results presented here show that substrate stiffness affects both cell adhesion and particle internalization, with softer substrates promoting higher levels of particle uptake. However, the activation of the CME pathway, either mechanically by particle size or functionally by receptor binding, regulates the sensitivity of cellular particle uptake to matrix stiffness. Finally, adeno-associated viruses as the leading platform for therapeutic gene delivery are used as model cargo to showcase the importance of considering multiple components when designing delivery systems. These findings indicate that particle uptake is a multifaceted process that can be improved by the appropriate combination of extracellular environment mechanics and cargo properties.